MODERNIZATION AND FUNCTIONING OF PRINCIPLES OF CIVIL PROCEDURAL LAW OF UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES - Voloshchenko, Olga (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2024)
Introduction. The signing of the association agreement between Ukraine and the European Union became a powerful impetus for the optimization of law-making processes aimed at improving domestic legislation. The series of commitments adopted by Ukraine regarding the imitation and fixation of European legislative values ​​in the domestic legal field has become a proper reference point for the legislator in matters of modernization and addition of existing provisions in the leading branches of law in general, and in the field of civil procedural law, in particular. Adoption of the new version of the Civil Procedure Code of Ukraine in 2017 was a major step in bringing the field of civil justice closer to the standards of the European Union and improving it. The review of the revised provisions in terms of the functioning and implementation of the principles of civil procedural law makes a positive impression in terms of compliance with the latest requirements of the practice of the European Court of Human Rights. Renewal of approaches to the understanding of the essence of some principles of civil justice led to the formation of new doctrinal conclusions on the basic meaning of such principles and their interaction.Summary of the main results. The doctrinal study of the processes of novelization of the principles of civil procedural law in the light of European integration processes made it possible to formulate the following theses: expanding the list of sources of civil procedural law, as a way of revising the principle of the Rule of Law, strengthened the latter both in the aspect of expanding the tools for ensuring the competitiveness of the process and in the processes of law-making and application practice; precedent practice of the Grand Chamber of the Supreme Court is considered as an element of legal certainty of the principle of the rule of law; it legally enshrined possibility of filing a claim using the "Electronic Court" services strengthened the principle of the Rule of Law in terms of ensuring human rights, as well as expanded the mechanisms of dominance and implementation of the principle of dispositiveness (in terms of the possibility of choosing methods of filing claims on the merits of the case, etc.); it was established that the establishment of the principle of proportionality in Article 11 of the Code of Criminal Procedure of Ukraine is an additional guarantee of ensuring the proper justification of the decision made by the judge (in the context of writing the motivational part of the court decision). Conclusion.The conducted doctrinal study of the content of the Civil Procedure Code of Ukraine through the prism of the practice of the ECtHR provided an opportunity to draw conclusions of general theoretical importance, which can be used in further scientific development of issues of the functioning and interaction of the principles of civil procedural law